Corneal higher-order aberrations after cataract surgery: Manual phacoemulsification versus femtosecond-laser assisted technique. Issue 6 (November 2021) - Pohlmann, Dominika; Pilger, Daniel; Bertelmann, Eckart; von Sonnleithner, Christoph
Purpose: To compare and evaluate corneal higher-order aberrations (c-HOA) between conventional manual phacoemulsification (Phaco), femtosecond laser-assisted cataract surgery (FLACS), and femtosecond laser-assisted cataract surgery with astigmatic keratotomy (FSAK). Methods: In this retrospective single center study, 53 healthy individuals with cataract (73 eyes) underwent phacoemulsification with implantation of an intraocular lens. Three groups were formed: group A, Phaco ( n  = 27 eyes of 21 patients); group B, FLACS ( n  = 25 eyes of 15 patients); group C, FSAK ( n  = 21 eyes of 17 patients). An iTrace aberrometer (Tracey Technologies, Houston, TX, USA) was used to perform aberrometry with a pupil scan size of 5.0 mm. We used ANOVA analysis and the paired sample t -test for statistical analysis. Results: There was no difference in total c-HOA between the groups prior to surgery ( F (2, 66) = 2.2, p  = 0.128), but some evidence for a difference between the groups after surgery (F(2, 65) = 3.87, p  = 0.025). After surgery, total c-HOA increased in all groups, but the greatest increase occurred FSAK. Conclusion: Manual phacoemulsification and femtosecond laser-assisted cataract surgery seem to have less impact on corneal higher-order aberrations than the combination of femtosecond laser-assisted cataract surgery with astigmatic keratotomy.